Assessing issues of change impact analysis process for a software projects - Ali, H.O. (2013)
Software Change Impact Analysis (SCIA) has defined as a process of identifying the consequences of the software changes requests. Almost no major corporations are free from the challenge of developing and implementing successful strategies for managing change. Different studies have been conducted in this subject for the last two decades, several approaches have been proposed. But most of these studies have less support to the current process of a software change management. The complexities of software change development nowadays cause the process of managing software change to be difficulty. There is major organizations that are free from the challenges of initiating, developing and implementing effective software changes management. As a result, software practitioners recognize that strategic change is not temporary issues but it's continued process. Only few project managers got the ability to manage th change efficiently. Therefore, this paper investigates issues of change impact analysis process and identifies and compares current practice issues of a software change impact analysis, by evaluating their strengths and weaknesses. It also reviews existing tools and models of change impact analysis and how it supports to the current software change managements. Hence, it proposes existing processe issues and suggests the need of an effective process of software change management. Â© IDOSI Publications, 2013.